Modification of titanium dioxide nanoparticle to enhance the photoactivity in visible light region - Wooi Chuan, Tan (2013)
In recent year, photocatalyst has been gaining a wide attention as the ability to harness the free energy from sunlight to perform variety of function such as organic degradation, solar cell and etc. When used as photocatalyst, titanium dioxide (TiO2) is able to absorb ultraviolet light only (UV) to initiate the oxidation and reduction which is able to speed up the degradation of dye. This thus provides a cheap and efficient method to solve the dye mismanagement that is face in industries these days. In this work, the titanium dioxide nanoparticle is modified via hydrazine wet method to increase photocatalytic activity. The photocatalytic activity is studied via methylene blue degradation, followed by the kinetic study on the methylene blue degradation. The catalyst has been characterized via UV-VIS spectrophotometer, FTIR machine and XRD machine. From the result, we realized that the main reaction that occurred during the modification is combustion of hydrazine on the surface of TiO2. From the UV-Vis spectrum, we found out that the modify catalyst can absorb more visible light as compare to the commercial TiO2. FTIR spectrum indicated that NHx group, NO group and an increase of OH group is presented after the modification. XRD pattern analysis suggested the crystallinity of the catalyst is slightly increased after the modification. Methylene blue degradation also showed that the modified catalyst have a higher activity as compared to the commercial one. The results obtained suggesting that the photocatalytic activity is increasing due to the ability of the catalyst to absorb visible light after the treatment. The modeling is done by relating the rate of methylene blue degradation with the direct hole attack and the hydroxyl radical attack occurred in the reaction